Ich - Du - Wir! Material zum kooperativen inklusiven Lernen. - Albers, Timm; Vanier, Dietlinde (Grundschule)

Inklusion - Bücher und Medien - Albers, Timm (Grundschule)

Qualität in der Bildung und Entwicklung unter 3. Sprachliche, emotionale und soziale Entwicklungsverläufe von Kindern in der Tagespflege und der Krippe unter der Zielperspektive von Inklusion: Abschlussbericht - Albers, Timm; Bendler, Sandra; Lindmeier, Bettina; Schröder, Claudia

Spielraum Bildung: Bedarfssteuerung und Angebotsgestaltung im Interesse behinderter Kleinstkind. Informationsdienst der Lebenshilfe für Menschen mit geistiger Behinderung Landesverband Niedersachsen e.V. 4 - Albers, Timm; Lindmeier, Bettina

Emilie Du Châtelet and the Transformation of Metaphysics - Hagengruber, Ruth Edith (Emilie Du Châtelet between Leibniz Und Newton)

Was ist und wozu Nanoethik? - Hagengruber, Ruth Edith; Dasch, Thomas

Lifelong Learning - auch für Lehrkräfte?! Angebote zur Fort- und Weiterbildung an Sprachenzentren - Behrent, Sigrid; Lorenz, Gunter (Excellent und initiativ. Qualitätsentwicklung und -sicherung in der Sprachausbildung an Hochschulen. Dokumentation der 26. Arbeitstagung 2010.)

The temperature as the real hot spot risk factor at PV-modules - Wendlandt, Stefan; Giese, Anne; Drobisch, Alex; Tomow, Dirk; Hanusch, Matthias; Berghold, Juliane; Krauter, Stefan; Grunow, Paul (Proceedings of the 27th European Photovoltaic Solar Energy Conference and Exhibition, Frankfurt a. M. (Germany), 24.-28. September 2012, pp. 3553-3557)

Zwischen Familie und Kirche, Fürstbistum und Reich: Identität(en) im Stiftsadel - Süßmann, Johannes (Facteurs d’Identité. Faktoren der Identität. Avec la collaboration d’Anna-Susan Franke)

Wurde der deutsche Adel galant? Vorüberlegungen zu den unerforschten Wegen des Galanterietransfers in der Adelserziehung des frühen 18. Jahrhunderts - Süßmann, Johannes (Die Kunst der Galanterie. Facetten eines Verhaltensmodells in der Literatur der Frühen Neuzeit)

Historicising the classics. How nineteenth-century German historiography changed the perspective on historical tradition - Süßmann, Johannes (Thucydides and the Modern World. Reception, Reinterpretation and Influence from the Renaissance to the Present)

Charakterisieren. Dilemma und Kunst der historiographischen Figurenzeichnung - Süßmann, Johannes (Figurenwissen. Funktionen von Wissen bei der narrativen Figurendarstellung)

[Art.] Donau - Süßmann, Johannes (Metzler Lexikon literarischer Symbole)

[Rez. v.] Jörg Ernesti: Ferdinand von Fürstenberg (1626–1683). Geistiges Profil eines barocken Fürstbischofs (=Studien und Quellen zur westfälischen Geschichte. 51). Paderborn: Bonifatius 2004 - Süßmann, Johannes (Paderborner Historische Mitteilungen)

Aufklärung und Hofkultur in Dresden. Jahrestagung der DGEJ in der Herzog August Bibliothek Wolfenbüttel, 11./12. November 2011. Tagungsbericht - Kanz, Roland; Süßmann, Johannes

122 GHz FMCW Radar Transceiver and Components in 0.13µm SiGe BiCMOS Technology - Scheytt, Christoph; Sun, Yaoming (System, MMIC and Package Design for Low-Cost Radar Sensor)

Spurs and Phase Noise for an integrated 8-12 GHZ Fractional-N PLL Synthesizer in SiGe BiCMOS - Koelnberger, Andreas; Herzel, Frank; Heyer, Heinz-Volker; Lia, Enrico; Piironen, Petri; Telle, Holger; Scheytt, Christoph (Simulations and Measurements of In-Band)

Was fördert affektives Commitment von Lehrkräften? Eine Analyse individueller und schulischer (Bedingungs-)Faktoren - Bloh, Bea; Gieske, Dipl; Gerick, Dipl.-Päd (Zeitschrift für Bildungsforschung)

How accurately do principals evaluate the strain experience of their teaching staff. - Bloh, Bea; van Ophuysen, Stefanie; Gerick, Julia; Gieske, Mario (The Journal of Educational Research)

Auf dem Weg zur gesunden Schule. - Bloh, Bea (Pädagogische Führung)

Polite Conversation, Implicatures, and Comical Effect: Jonathan Swift and P. G. Wodehouse - Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

New Perspectives on Imaginary Dialogues: An Interdisciplinary Dialogue - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

Second-Person Narration in Literary and Conversational Storytelling - Mildorf, Jarmila (Storyworlds)

Der Wiener Kongress als „Kinderstube“ des Philhellenismus: das Beispiel des Bankiers Jean-Gabriel Eynard - Schönhärl, Korinna; Kerschbaumer, Florian (Forum Vormärz-Forschung)

Der Georgeaner Kurt Singer in Japan: „Die aber wie der Meister sind, die gehen, und Schönheit wird und Sinn wohin sie sehen.“ - Schönhärl, Korinna; Schefold, Bertram (Studien zur Entwicklung der ökonomischen Theorie XXVII)

Imaginary Dialogues in English: Explorations of a Literary Form

Die griechische Staatsverschuldung in der zweiten Hälfte des 19. Jahrhunderts - Schönhärl, Korinna; Psalidopoulos, Michalis (Vom Wohl und Wehe der Staatsverschuldung. Erscheinungsformen und Sichtweisen von der Antike bis zur Gegenwart)

Strukturelle Wirtschafts- und Finanzprobleme Griechenlands im 19. Jahrhundert - Schönhärl, Korinna (Hellenika. Jahrbuch für griechische Kultur und deutsch-griechische Beziehungen)

Solving multiobjective optimal control problems in space mission design using discrete mechanics and reference point techniques - Ober-Blöbaum, Sina; Ringkamp, M.; zum Felde, G. (51st IEEE International Conference on Decision and Control)

Handling high dimensional problems with multi-objective continuation methods via successive approximation of the tangent space - Ringkamp, M.; Ober-Blöbaum, Sina; Dellnitz, M.; Schütze, O. (Engineering Optimization)

Trajectory design combining invariant manifolds with discrete mechanics and optimal control - Moore, A.; Ober-Blöbaum, Sina; Marsden, J. E. (Journal of Guidance, Control, and Dynamics)

Solving optimal control problems by exploiting inherent dynamical systems structures - Flaßkamp, K.; Ober-Blöbaum, Sina; Kobilarov, M. (Journal of Nonlinear Science)

Switching time optimization in discretized hybrid dynamical systems - Flaßkamp, K.; Murphey, T.; Ober-Blöbaum, Sina (51st IEEE International Conference on Decision and Control)

Motion planning for mechanical systems with hybrid dynamics - Flaßkamp, K.; Ober-Blöbaum, Sina (Progress in Industrial Mathematics at ECMI 2012, Mathematics in Industry (To appear))

Higher order variational time discretization of optimal control problems - Campos, C.M.; Junge, O.; Ober-Blöbaum, Sina (20th International Symposium on Mathematical Theory of Networks and Systems)

Energy efficient control for mechanical systems based on inherent dynamical structures - Flaßkamp, K.; Ober-Blöbaum, Sina (American Control Conference)

Optimal Control on Stable Manifolds for a Double Pendulum - Flaßkamp, Kathrin; Timmermann, Julia; Ober-Blöbaum, Sina; Dellnitz, Michael; Trächtler, Ansgar (Proceedings in Applied Mathematics and Mechanics)

Securing the reliability of tomorrow's systems with Self-Optimization - Pook, Sebastian; Gausemeier, Jürgen; Dorociak, Rafal (The Annual Reliability and Maintainability Symposium RAMS 2012)

System for the design of production systems based on the principle solution{\"solution} of mechatronic systems. - Nordsiek, Daniel

Systematik zur effizienten Bildung geospezifischer Umgebungsmodelle für Fahrsimulationen. - Kreft, Sven

A New Systems Engineering Approach as Enabler for Early Sustainability Analysis - Gausemeier, Jürgen; Rudtsch, Vinzent; Tschirner, Christian (Proceedings of the GCSM 2012 10th Global Conference on Sustainable Manufacturing, Istanbul, Turkey, November)

Management of Cross-Domain Model Consistency for Behavior models of Mechatronic Systems - Rieke, Jan; Dorociak, Rafal; Sudmann, Oliver; Gausemeier, Jürgen; Schäfer, Wilhelm (Proceedings of the International Design Conference – DESIGN)

Preventive product protection - guidelines and application examples - Gausemeier, Jürgen; Lindemann, Udo; Glatz, Rainer
Product piracy destroys jobs, deprives industry of the return on research and development investments and threatens the competitiveness of many companies. Protection against product imitations requires the development of innovative, technical protective measures and holistic protection concepts. This work shows how such protection concepts are developed and implemented. Central to this are the identification of the individual threat potential and the implementation of comprehensive product protection based on protective measures. Practical examples illustrate the application of the methods and tools and facilitate the practical transfer. A uniform presentation of over 90 protective measures completes the book.

Design Framework for the Integration of Cognitive Functions into Intelligent Technical Systems - Dumitrescu, Roman; Anacker, Harald; Gausemeier, Jürgen (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Predicting the future of additive manufacturing – scenario-based comparison of technology push and market pull - Gausemeier, Jürgen; Echterhoff, Niklas; Wall, Marina (Electronic proceedings of the Rapid.Tech 2012)

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

A Framework for the Improvement of Dependability of Self-Optimizing Systems - Dorociak, Rafal; Gaukstern, Tobias; Gausemeier, Jürgen; Iwanek, Peter (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Intelligent Technical Systems OstWestfalenLippe - Dumitrescu, Roman; Jürgenhake, Christoph; Gausemeier, Jürgen (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Cost-Benefit-Analysis – Requirements for the Evaluation of Self-Optimizing Systems - Vaßholz, Mareen; Gausemeier, Jürgen (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Technology Push Based Product Planning – Thinking ahead – Future Markets for Emerging Technologies - Gausemeier, Jürgen; Wall, Marina; Peitz, Christoph; Echterhoff, Niklas

Pr ä ventiver product protection - guidelines and application examples - Gausemeier, J {\ "u} rgen; Lindemann, Udo; Glatz, Rainer
Product piracy destroys jobs, deprives industry of the returns on its research and development investments and threatens the competitiveness of many companies. To protect against product imitations, innovative, technical protective measures and holistic protection concepts must be developed. This work shows how such protection concepts are developed and implemented. Central to this are the identification of the individual threat potential and the implementation of comprehensive product protection based on protective measures. Practical examples illustrate the application of the methods and tools and facilitate the transfer into practice. A uniform presentation of over 90 protective measures rounds off the book.

Thinking ahead of the future of additive manufacturing - scenario-based comparison of technology push and market pull - Gausemeier, J {\ "u} rgen; Echterhoff, Niklas; Wall, Marina

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Market and environmental scenarios in medical electronics - requirements for the products and services of tomorrow - Gausemeier, J {\ "u} rgen; Lehner, Markus

Technology Push Based Product Planning – Thinking ahead – Future Markets for Emerging Technologies - Gausemeier, Jürgen; Wall, Marina; Peitz, Christoph; Echterhoff, Niklas

Discipline {\ "u} comprehensive, model-based development - integrative conception of product and production system - Brandis, Rinje (Digital Engineering Magazin)

Cross-discipline, model-based development - integrative conception of product and production system - Brandis, Rinje (Digital Engineering Magazin)

Thinking ahead the Future of Additive Manufacturing – Future Applications - Gausemeier, Jürgen; Echterhoff, Niklas; Kokoschka, Martin; Wall, Marina

Thinking ahead the Future of Additive Manufacturing – Future Applications - Gausemeier, Jürgen; Echterhoff, Niklas; Kokoschka, Martin; Wall, Marina

Systematik zur Konzipierung von Produktionssystemen auf Basis der Prinziplösung mechatronischer Systeme. - Nordsiek, Daniel

Systematik zur effizienten Bildung geospezifischer Umgebungsmodelle für Fahrsimulationen - Kreft, Sven

Design Framework for the Integration of Cognitive Functions into Intelligent Technical Systems - Dumitrescu, Roman; Anacker, Harald; Gausemeier, Jürgen (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

A Framework for the Improvement of Dependability of Self-Optimizing Systems - Dorociak, Rafal; Gaukstern, Tobias; Gausemeier, Jürgen; Iwanek, Peter (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Intelligent Technical Systems OstWestfalenLippe - Dumitrescu, Roman; Jürgenhake, Christoph; Gausemeier, Jürgen (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Securing the reliability of tomorrow's systems with Self-Optimization - Pook, Sebastian; Gausemeier, Jürgen; Dorociak, Rafal

Cost-Benefit-Analysis – Requirements for the Evaluation of Self-Optimizing Systems - Vaßholz, Mareen; Gausemeier, Jürgen (Proceedings of 1st Joint International Symposium on System-integrated Intelligence: New Challenges for Product and Production Engineering)

A New Systems Engineering Approach as Enabler for Early Sustainability Analysis - Gausemeier, Jürgen; Rudtsch, Vinzent; Tschirner, Christian (Proceedings of the GCSM 2012 10th Global Conference on Sustainable Manufacturing, Istanbul, Turkey, November)

Management of Cross-Domain Model Consistency for Behavior models of Mechatronic Systems - Rieke, Jan; Dorociak, Rafal; Sudmann, Oliver; Gausemeier, Jürgen; Schäfer, Wilhelm (Proceedings of the International Design Conference – DESIGN)

Early Probabilistic Reliability Analysis of Mechatronic Systems - Dorociak, Rafal

An Automatic Approach for Parameter Optimization of Material Flow Simulation Models based on Particle Swarm Optimization - Laroque, Christoph; Pater, Jan-Patrick
The analysis of production systems by the use of discrete, event-based simulation is widely used and accepted as decision support method. It aims either at the comparison of competitive designs or the identification of a “best possible” configuration of the simulation model. Here, combinatorial techniques of simulation and optimization methods support the user in finding optimal solutions, which typically result in long computation times and though often prohibit a practical application in today’s industry. This paper presents a fast converging procedure as a combination of a swarm heuristic, namely the particle swarm optimization, and the material flow simulation to close this gap. Faster convergence is realized by a specific extension of classic PSO implementations. First results show the applicability with a simulation reference model.

Multi-Layer Architecture for Transition of Business-Models to common Software-Tools and Optimization of the Model-Structure exemplified with Microsoft SharePoint 2010 - Lauck, Sebastian; Hartmann, Philip; Laroque, Christoph

Fast Converging, Automated Experiment Runs for Material Flow Simulations Using Distributed Computing and Combined Metaheuristics - Laroque, Christoph; Klaas, Alexander; Fischer, Jan-Hendrik; Kuntze, Mathis (Proceedings of the 2012 Winter Simulation Conference)

Application relevance of dissertations - Dangelmaier, Wilhelm

Bi-objective-optimisation of an international transportation problem for CO2-efficient schedules - Kl{\, Benjamin; Pater, Jan-Patrick; Irohara, Takashi; Xue, Yudong (International Journal of Engineering Management and Economic)
The transportation sector accounts for a considerable portion of global CO2 emissions and the demand for transport, especially for international transport, is increasing. Current approaches to reduce CO2 emission on an operational level ignore time-related objectives and focus on simultaneous optimisation of economic and ecological objectives. In general, considering the minimisation of CO2 emissions in transportation scheduling introduces a trade-off between economic and ecological concerns. The concept of eco-efficiency is important in order to evaluate the economical value and ecological quality of business decisions. Nevertheless, this concept has primarily been applied to strategic decisions. In the present paper we demonstrate the applicability of this concept to operative decisions and introduce a bi-objective evolutionary optimisation approach for the approximation of CO2-efficient schedules in an international transportation problem.

Visualization and Collaborative Editing of Simulation Models With Heterogeneous Clients - Implemented Into the Simulator d3fact - Renken, Hendrik; Eichert, Felix Alexander; Brandt, Sascha; Klaas, Alexander

Development of cost-effective spare parts logistics for a solar technology provider under monet {\ "a} rer Ber ü consideration of resulting CO2 emissions - Dangelmaier, Wilhelm; Laroque, Christoph; Delius, Robin; Streichhan, Jenny

Kontinuierliche Adaption von Lieferketten durch Leistungsbewertung und -steuerung dynamischer Geschäftsprozesse - Hartmann, Philip; Laroque, Christoph

Comparing a hybrid simulation & optimization approach with a purely stochastic optimization to increase the robustness of production plans - Fischer, Jan-Hendrik; Delius, Robin; Horstkemper, Dennis; Laroque, Christoph

Increase of robustness in production plans using a hybrid optimization and simulation approach - Laroque, Christoph; Delius, Robin; Fischer, Jan-Hendrik (International Journal on Advances in Systems and measurements)

Parallel scheduling for evolving manufacturing systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 9th IEEE International Conference on Industrial Informatics)

Building blocks of business informatics - basics and applications - Fischer, J; Dangelmaier, Wilhelm; Nastansky, Ludwig; Suhl, L

Robust solution approach to an uncertain CLSP problem - Kaganova, Ekaterina (Applied Mathematical Optimization and Modelling)

A multi-objective evolutionary approach to scheduling for evolving manufacturing systems - Kl{\, Benjamin; Pater, Jan-Patrick; Honiden, Shinichi; Dangelmaier, Wilhelm (Evolving Systems)
Persistent trends like quickly changing production programs, increasing customer individual manufacturing and Sustainable Manufacturing create complex systems of objectives in manufacturing control. Service-oriented manufacturing systems and self-optimizing manufacturing resources offer the required flexibility to consider these objectives in accordance with the current organizational and economical situation. On the downside, this increase in flexibility make the control of manufacturing systems more difficult and presents new challenges regarding the scheduling. To meet these challenges, we developed scheduling framework that supports alternative process plans and considers the internal states trajectories of resources. In order to support the user in a complex decision-making environment, evolutionary multi-objective optimization is used to generate a set of relevant schedules and an interface to select the most appropriate schedule is provided.

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference,)

Ensuring calls to automotive suppliers with minimal costs with special consideration of liquidity {\ "a} ts-, Besch {\ "a} qualification, know-how and IT restrictions - Delius, Robin

A Cross-Level Approach To Planning Changeability in Distribution Systems - Klingebiel, Katja; Winkler, Matthes; Klaas, Alexander; Laroque, Christoph (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Effektives Customer Relationship Management: Instrumente - Einführungskonzepte - Organisation - Helmke, Stefan, Stefan; Uebel, Matthias; Dangelmaier, Wilhelm

Proceedings of the 2012 Winter Simulation Conference

A model for dimensioning a secure event-driven health care system - Sánchez-Guerrero, Rosa; Almenárez, Florina; Díaz Sánchez, Daniel; Arias Cabarcos, Patricia; Marín, Andrés (5th Joint IFIP Wireless and Mobile Networking Conference, WMNC 2012, Bratislava, Slovakia, September 19-21, 2012)

A H.264 SVC distributed content protection system with flexible key stream generation - Díaz Sánchez, Daniel; Sánchez Guerrero, Rosa; Marín López, Andrés; Almenárez, Florina; Arias Cabarcos, Patricia (IEEE Second International Conference on Consumer Electronics - Berlin, ICCE-Berlin 2012, Berlin, Germany, September 3-5, 2012)

Private cloud and media privacy in social networks - Marín López, Andrés; Díaz Sánchez, Daniel; Almenárez Mendoza, Florina; Arias Cabarcos, Patricia; Sánchez-Guerrero, Rosa; Sanvido, Fabio (IEEE Second International Conference on Consumer Electronics - Berlin, ICCE-Berlin 2012, Berlin, Germany, September 3-5, 2012)

SuSSo: Seamless and ubiquitous single sign-on for cloud service continuity across devices - Arias Cabarcos, Patricia; Almenárez Mendoza, Florina; Sánchez-Guerrero, Rosa; Marín López, Andrés; Díaz Sánchez, Daniel (IEEE Trans. Consumer Electron.)

A Metric-Based Approach to Assess Risk for "On Cloud" Federated Identity Management - Arias Cabarcos, Patricia; Almenárez Mendoza, Florina; Marín López, Andrés; Díaz Sánchez, Daniel; Sánchez-Guerrero, Rosa (J. Netw. Syst. Manag.)

Enhancing privacy and dynamic federation in IdM for consumer cloud computing - Sánchez-Guerrero, Rosa; Almenárez, Florina; Arias Cabarcos, Patricia; Díaz Sánchez, Daniel; Marín, Andrés (IEEE Trans. Consumer Electron.)

An Event Driven Hybrid Identity Management Approach to Privacy Enhanced e-Health - Sánchez-Guerrero, Rosa; Almenárez, Florina; Díaz Sánchez, Daniel; Marín, Andrés; Arias Cabarcos, Patricia; Sanvido, Fabio (Sensors)

A distributed transcoding system for mobile video delivery - Díaz Sánchez, Daniel; Marín López, Andrés; Almenárez, Florina; Sánchez-Guerrero, Rosa; Arias Cabarcos, Patricia (5th Joint IFIP Wireless and Mobile Networking Conference, WMNC 2012, Bratislava, Slovakia, September 19-21, 2012)

Multi-device Single Sign-on for cloud service continuity - Arias Cabarcos, Patricia; Almenárez, Florina; Sánchez-Guerrero, Rosa; Marín, Andrés; Díaz Sánchez, Daniel (IEEE International Conference on Consumer Electronics, ICCE 2012, Las Vegas, NV, USA, January 13-16, 2012)

Privacy enhanced cloud services home aggregator - Sanvido, Fabio; Díaz Sánchez, Daniel; Sánchez-Guerrero, Rosa; Almenárez, Florina; Arias Cabarcos, Patricia (IEEE International Conference on Consumer Electronics, ICCE 2012, Las Vegas, NV, USA, January 13-16, 2012)

Trust-aware federated IdM in consumer cloud computing - Sánchez-Guerrero, Rosa; Arias Cabarcos, Patricia; Almenárez Mendoza, Florina; Díaz Sánchez, Daniel (IEEE International Conference on Consumer Electronics, ICCE 2012, Las Vegas, NV, USA, January 13-16, 2012)

Positive Beispiele zu negativen Zahlen - Unterrichtsstudien zum Mathematikunterricht - Althoff, Paula G.; Friedli, Reto; Hattermann, Mathias; Vom Hofe, Rudolf; Kullmann, Harry; Viehmeister, Frauke (Laborschulforschung 2012. Berichte und Neuanträge im Forschungs- und Entwicklungsplan. Werkstattheft Nr. 47)